Education Policies and Migration across European Countries - Ainhoa Aparicio Fenoll; Zoë Kuehn (Institute for the Study of Labor (IZA), 2016)
This paper tests whether and how two education policies: (i) increasing the length of compulsory education and (ii) introducing foreign languages into compulsory school curricula, affect subsequent migration across European countries. We construct a novel data base that includes information on education reforms for thirty-one countries spanning four decades. Combining this data with information on recent migration flows by cohorts, we find that an additional year of compulsory education reduces the number of emigrants by almost 10%. Increasing the length of compulsory education shifts educational attainment for a significant fraction of the population from low towards medium levels. Our findings are thus in line with the fact that in the majority of European countries medium educated individuals display lower emigration rates than low educated individuals. Introducing a foreign language into compulsory school curricula on the other hand, almost doubles the number of emigrants to the country where the language is spoken and increases the total number of emigrants by 20%. Depending on the specific content of an education policy, "more education" can thus have opposite effects on migration.
Keywords: J61; I20; F22; 330; migration; compulsory schooling; foreign language proficiency; education